Psychological Resilience, Cardiovascular Disease, and Metabolic Disturbances: A Systematic Review - Ghulam, Anwal; Bonaccio, Marialaura; Costanzo, Simona; Bracone, Francesca; Gianfagna, Francesco; de Gaetano, Giovanni; Iacoviello, Licia (Frontiers in Psychology, 2022)
Background. Psychosocial factors play an important role in cardiovascular disease (CVD) development, one of these, psychological resilience (PR) is defined as the capacity of responding positively to stressful events. Our aim was to assess whether PR is associated with CVD and metabolic disturbances through a systematic review. Methods. We searched PubMed, Web of Science, PsycInfo and Google Scholar up to 7/7/2021. Included articles were in English, were observational and had PR examined as exposure. The main CVD outcomes were either clinical or metabolic outcomes (dyslipidaemia, obesity, metabolic syndrome, hypertension, and diabetes). Results. Literature search identified 3,800 studies, 17 met the inclusion criteria. Of them, seven were longitudinal and 10 cross-sectional, 13 were on adults and four on children. Exposure assessment was heterogeneous among studies, while regarding outcomes, five studies investigated CVD, seven obesity, one metabolic syndrome, two hypertension, four dyslipidaemia and four diabetes. In longitudinal studies, PR was found to have an inverse association with included outcomes in 5 cohorts from the Swedish military conscription but had no association with CVD in an African-American women cohort, and was associated with better progression of diabetes. In most cross-sectional studies PR was inversely associated with the included outcomes except obesity that showed mixed results Conclusions. PR seems to have a possibly favourable association with CVD and metabolic disturbances, that differs according to type of outcome and population. Limitations are given by the small number of studies available and the heterogeneity in PR measurement.